1998
DOI: 10.1007/s003390051186
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the initial oxidation of cobalt in alkaline solutions using scanning electrochemical microscope

Abstract: Scanning electrochemical microscopy and atomic force microscopy were used together with cyclic voltammetry and rotating ring disc experiments to study the initial oxidation of cobalt in alkaline solution. The results show that the mechanism of cobalt oxidation involves a solid state path as well as dissolution combined with precipitation. In the concentration region studied, 0.1-1 M NaOH, the solid state path seems to predominate.The AFM images clearly show a three-dimensional growth mechanism and that the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 3 publications
3
17
0
Order By: Relevance
“…EDS was performed to measure the compositional changes as a function of cycling. A 2% decrease in Co content relative to Pd was recorded after 20 cycles in a solution containing KOH only, and a 4% decrease in Co fraction was recorded in KOH with ethanol; these values are consistent with an average loss of 3% Co to soluble Co(OH) 2 species as reported by Erts et al for a concentrated KOH solution [44]. The limited compositional variation indicates that no significant dealloying of the films occurs.…”
Section: Electrocatalytic Activity Of Pdeco Alloy Filmssupporting
confidence: 55%
“…EDS was performed to measure the compositional changes as a function of cycling. A 2% decrease in Co content relative to Pd was recorded after 20 cycles in a solution containing KOH only, and a 4% decrease in Co fraction was recorded in KOH with ethanol; these values are consistent with an average loss of 3% Co to soluble Co(OH) 2 species as reported by Erts et al for a concentrated KOH solution [44]. The limited compositional variation indicates that no significant dealloying of the films occurs.…”
Section: Electrocatalytic Activity Of Pdeco Alloy Filmssupporting
confidence: 55%
“…4 over a range of electrolyte concentrations from 0.25 M 6 [OH À ] 6 5.0 M, are included as supplementary data and confirm the aforementioned trend. In addition it is worth noting that Erts et al [62] detected no soluble species using either RRDE or SECM, when they studied Co in 0.1 M NaOH solution.…”
Section: Cobalt: Voltammetry and Steady State Polarisationmentioning
confidence: 97%
“…For the more concentrated electrolyte, the marked decrease over the first few cycles in the charge capacity of this peak, is believed [33,51,52,54] to be related to Co dissolution occurring simultaneously to passive film formation. Based on a combination of rotating ring disc electrode (RRDE) and scanning electrochemical microscopy (SECM) measurements, Erts et al [62] proposed that the initial passivation of Co in this region of potential (1 M NaOH) occurs via a rapid dissolution/precipitation mechanism. However, the developing anodic oxide soon stabilises the system with respect to dissolution -note the similarity in the A II profiles for the 10th and 100th cycles.…”
Section: Cobalt: Voltammetry and Steady State Polarisationmentioning
confidence: 99%
“…This latter assignment is based on the results of a series of rotating ring disk electrode (RRDE) and scanning electrochemical microscopy (SECM) studies performed by Behl and Toni 224 and Erts et al 228 In their RRDE studies, Behl and Toni 224 observed small but significant amounts of dissolved Co 2+ species, the concentration of which reached a maximum at potentials just below those corresponding to peak II in Fig. 13.…”
Section: Interfacial Redox Chemistry Of Cobalt Based Electrodes In Almentioning
confidence: 99%